Effect of Parental Involvement on Children’s Academic Achievement in Chile - Lara, Laura; Saracostti, Mahia (Frontiers in Psychology, 2019)
Parental involvement in school has been demonstrated to be a key factor for children’s academic outcomes. However, there is a lack of research in Chile, as well as in Latin American countries in general, leaving a gap in the literature about the generalization of findings outside developed and industrialized countries, where most of the research has been done. The present study aims to analyse the associations between parental involvement in school and children’s academic achievement. Cluster analysis results from a sample of 498 parents or guardians whose children attended second and third grades in 16 public elementary schools in Chile suggested the existence of three different profiles of parental involvement (high, medium and low) considering different forms of parental involvement (at home, at school and through the invitations made by the children, the teachers and the school). Results show that there are differences in children’s academic achievement between the parental involvement profiles, indicating children whose parents have a low involvement have lower academic achievement. Findings are in line with international research evidence, suggesting the need to focus on this variable too in Latin American contexts.